2019
DOI: 10.2131/fts.6.217
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of increased weights of the liver and kidneys by cessation of D-allulose feeding in Wistar rats

Abstract: Rare sugar D-allulose prevents obesity; however, an excessive and continuous intake of D-allulose may induce weight increases in the liver and kidney without apparent pathological and functional abnormalities. Conversely, there has not been reported about how these parameters will change after cessation of D-allulose intake. In this study, effects of a 10-week D-allulose cessation on liver and kidneys weights and biomarkers were investigated in rats previously fed a D-allulose containing diet for 4 weeks. Wist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, D-allulose has been reported to suppress elevation of postprandial blood glucose (Hayashi et al, lulose acts by inhibiting α-glucosidase activity (Matsuo and Izumori, 2006) and increasing glucose uptake to the liver by facilitating glucokinase translocation from the nucleus to the cytoplasm in the liver (Hossain et al, 2011). D-allulose has already been clarified not to cause mutagenesis nor toxicity (Matsuo et al, 2002;Ochiai et al, 2019). The maximum non-effective level of D-allulose in causing diarrhea in human subjects was approximately 0.50-0.60 g per kg body weight (Iida et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, D-allulose has been reported to suppress elevation of postprandial blood glucose (Hayashi et al, lulose acts by inhibiting α-glucosidase activity (Matsuo and Izumori, 2006) and increasing glucose uptake to the liver by facilitating glucokinase translocation from the nucleus to the cytoplasm in the liver (Hossain et al, 2011). D-allulose has already been clarified not to cause mutagenesis nor toxicity (Matsuo et al, 2002;Ochiai et al, 2019). The maximum non-effective level of D-allulose in causing diarrhea in human subjects was approximately 0.50-0.60 g per kg body weight (Iida et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study of chronic toxicity using rats, the administration of 3% D-allulose resulted in kidney hypertrophy without any adverse health effects (Yagi & Matsuo, 2009). In addition, we suggested that feeding rats a diet containing 3% D-allulose for 4 weeks could increase the weights of the liver and kidney without any pathological damage, while 10 weeks of D-allulose interruption reversed these effects (Ochiai et al, 2019). In a clinical study evaluating 12-week ingesting of an isomerized carbohydrate containing 6% D-allulose, Hayashi et al (2014) reported the absence of adverse effects on studies of lipid and carbohydrate metabolism or abnormal blood parameters, and renal and hepatic functions.…”
Section: Discussionmentioning
confidence: 85%